2010
DOI: 10.1021/ja102105q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Morphological Control, and Antibacterial Properties of Hollow/Solid Ag2S/Ag Heterodimers

Abstract: Ag(2)S and Ag are important functional materials that have received considerable research interest in recent years. In this work, we develop a solution-based synthetic method to combine these two materials into hollow/solid Ag(2)S/Ag heterodimers at room temperature. Starting from monodisperse Cu(2)O solid spheres, CuS hollow spheres can be converted from Cu(2)O through a modified Kirkendall process, and the obtained CuS can then be used as a solid precursor for preparation of the Ag(2)S/Ag heterodimers throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
239
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(260 citation statements)
references
References 91 publications
21
239
0
Order By: Relevance
“…17,47 As reported, disruption to the membrane electron-transport chain will cause toxicity to bacteria. 18,48 This is similar to the vanadium-induced toxicity on cellular mitochondria. 46,49 As discussed earlier, the exposure of bacteria to V metal, V 2 O 3 , VO 2 , and V 2 O 5 nanofilms may elevate intracellular ROS levels and thus cause oxidative stress and damage.…”
supporting
confidence: 56%
“…17,47 As reported, disruption to the membrane electron-transport chain will cause toxicity to bacteria. 18,48 This is similar to the vanadium-induced toxicity on cellular mitochondria. 46,49 As discussed earlier, the exposure of bacteria to V metal, V 2 O 3 , VO 2 , and V 2 O 5 nanofilms may elevate intracellular ROS levels and thus cause oxidative stress and damage.…”
supporting
confidence: 56%
“…The room-temperature diffusion of metals (e.g., Au) into semiconductors to form metal-semiconductor pairs generally occurs at the nanometer scale when the semiconductor band-gap energy is lower than about 2.5 eV. [ 16,17 ] Figure S5 showed the simplifi ed band structures of Ag 2 S. The band gap is about 0.9 eV for bulk Ag 2 S crystal at room temperature, and 1.4-2.3 eV for those nanostructured Ag 2 S. [ 24 ] As a result, the diffusion of metals (Au and Ag) in the AuAg-Ag 2 S nanowires agrees with the aforementioned diffusion criteria. The Ostwald ripening between the initially formed Ag 2 S grains can occur because of the diffusion of metals, so that larger segments grow at the expense of nearby smaller grains.…”
mentioning
confidence: 99%
“…23 and 514-531 nm of the Ag 2 S/Ag heterostructures. 7 The weak SPR observed herein indeed suggested that the good contact between the Ag 2 S and Ag segments might ensure an effective charge transfer across the phase boundary, and changes in the structure and shape of the product. When the time was increased to 8 h, the SPR absorption bands of the Ag NWs almost disappeared owing to their further sulfuration, and the characteristic absorption feature of Ag 2 S moved to the longer wavelength region at around 515 nm.…”
Section: Resultsmentioning
confidence: 54%